Spectral Properties of Laplacians on Snowflake Domains and Filled Julia Sets. Issue 3 (31st August 2022) - Strichartz, Robert S.; Wiese, Samuel C.
Abstract: We present eigenvalue data and pictures of eigenfunctions of the classic and quadratic snowflake fractal and of quadratic filled Julia sets. Furthermore, we approximate the area and box-counting dimension of selected Julia sets to compare the eigenvalue counting function with the Weyl term.